It Went Downhill From There: The Spillover Effect from Previous Customer Mistreatment on Frontline Employees' Service Delivery. (August 2022) - Yue, Yumeng; Wang, Karyn L.; Groth, Markus
Research indicates that a customer's service experience is shaped by their past experiences with the firm. However, the extent to which past experiences with customers shape frontline service employees' delivery of services has not been examined. We propose that the analysis of service encounters as discrete, independent units ignores possible linkages between customer experiences via frontline employees. Adopting a resource spill-over perspective across two studies, we find that employees' experience of customer mistreatment compromised their subsequent service delivery. Using an experiment in Study 1, we find that these effects are mediated by changes in the employee's self-control capacity. Using a field sample in Study 2, we find that these effects are moderated by the employee's dispositional self-control capacity and their motivation to commit to display rules. Our findings show how service encounter outcomes can be shaped by distal service events and call for a more holistic understanding of the forces that shape service encounter outcomes. In particular, by highlighting the potential consequences, our findings challenge conventional work protocols that compel employees to persevere despite their experience of mistreatment. By detailing the mediating and moderating mechanisms of mistreatment spill-over in service organizations, we highlight the recovery mechanisms and practices that enable FLEs to remain resilient despite negative encounters with customers.